Characterization of Corynebacterium pseudotuberculosis from Sudan by Multiplex PCR (Journal of Veterinary Medicine and Animal Production, 2023)
A multiplex PCR(mPCR) was used to examine isolates of Corynebacterium pseudotuberculosis from cases of caseous lymphadenitis in sheep and goats in South Darfur State, Western Sudan. Using primers targeting the 16S rRNA, pld and rpoBgenes, electrophoresis of the DNA of the isolates showed homogeneity of these targeted genes. The mPCR could be used for rapid and accurate diagnosis of the disease in sheep and goats which may help in its control.